Airfare pricing strategies between full service carrier and low cost carrier : the opposing price trend effect - Ang, Chin Pei (2012)
With the increasing presence of Low Cost Carriers in the Aviation Industry, airlines would be concerned about the resulting competitive effects these carriers have on their business. Hence, this paper aims to analyse whether the current pricing strategies of both Low Cost Carriers and Full Service Carriers are profit maximising. This paper will also find out whether it is true that Low Cost Carriers tend to increase their airfares closer to departure dates while Full Service Carriers tend to decrease their airfares close to departure dates. Firstly, our study uncovers some factors that can affect airfares. Specifically, the number of days before departure can warrant drastic changes in airfares. Thus, airfares are tracked on a daily basis and the data collected are regressed using two theoretical models that we have developed. Results have shown that our proposition of the price trend holds for airlines competing on the same routes. However, our findings from the model, which incorporated Bertrand competition, did not show a significant level of competition between Low Cost Carriers and Full Service Carriers. Given these findings, our paper concludes that the current airfares offered are a result of profit maximising behaviours of both carriers.